Investigating the Relationship Between FMS Test Scores and the Occurrence of Injury in Elite Female Shooter - Abdolrasoul Daneshjoo; Baran Hoseini; Fatemeh Ghasemi (Islamic Azad University, Hamedan Branch, 2022)
Objective: The purpose of this study was to investigate the relationship between functional motor test scores and injury incidence in elite Tehranian female shooting athletes. Methods: The statistical population of this quasi-experimental study was all elite athletes and super league shooters (guns & rifles) in Tehran in 1398. The sample consisted of 40 individuals (20 with a history of injury and 20 without injury) who, using G Power software, were purposefully selected after public recall. After obtaining the consent form and measuring the demographic characteristics of the subjects, a checkerboard method and a New York test questionnaire were used to measure the variables of the study. All subjects performed the seven Functional Movement Screen (FMS) after evaluating the degree of stature abnormalities. After checking the normality of the data via Shapiro-Wilk test, they were analyzed through independent t-test and Pearson correlation coefficient using SPSS software with α = 0.05. Results: The findings of the present study showed that, in the athletes with an injury record, there was a significant negative relationship between the total score of functional movement screen and the occurrence of scoliosis (P = 0.001), uneven shoulder (P = 0.044) and uneven pelvis (P = 0.001) and no significant relationship was observed in athletes without a history of injury (P≤0.05). Also, there was no significant relationship between total score of functional movement screen and the incidence of cervical injury (P = 0.661, P = 0.001) in subjects with and without history of injury. Conclusion: According to the results, the motor-functional test scores provide the trainers and therapists with a good prevention model of traumatic injuries and disorders such as scoliosis, uneven shoulder and uneven pelvis. Therefore, it is recommended that trainers and athletes in this field use Functional Examinations (FMS) along with clinical diagnostic tests to improve and prevent these injuries.